CONTINUOUS GLUCOSE MONITORING (CGM) PADA KEGAWATDARURATAN DIABETES MELLITUS (HIPOGLIKEMIA): LITERATURE REVIEW - Nurul Hidayah; Robiul Fitri Masithoh (LPPM Universitas BSI, 2021)
Continuous Glucose Monitoring (CGM) is a tool to detect blood glucose levels in Diabetes Mellitus patients, and in this case also causes hypoglycemia. Hypoglycemia is an emergency that must be treated immediately. Patients who have emergency conditions such as hypoglycemia should have their blood glucose levels monitored. The purpose of this study was to determine the use of Continuous Glucose Monitoring (CGM) in Diabetes Mellitus (Hypoglycemia) emergencies. There are several types of Continuous Glucose Monitoring (CGM) offered by several distributors, but these types have the same function, which is to help patients, their families, and the health team to determine the patient's current health condition. This research method uses a literature review study using PubMed, ScienceDirect, ProQuest, and ClinicalKey. The results of the study contained 5 articles that matched the inclusion and exclusion criteria of the researcher.